Sri Aman Resident Office / Dayang Suhaila Abang Mohd Porkan - Abang Mohd Porkan, Dayang Suhaila (Univesiti Teknologi MARA Cawangan Sarawak, 2015)
Sri Aman Resident Office was officially been established on 1st June 1873 and was locate on Alice Fort. Resident Office which signifying the authority of state government of Sarawak has ratifying the Alice Fort as the headquarters. James Brooke Crookshank was appointed as the first Resident in Simanggang. Afterward, Resident Office vacated the Alice Fort and moved to the area which opposite the Alice Fort. Then, the Resident Office moved to level two and three of State Government Office Complex on 1st March 1971 in which now are being used by District Office Sri Aman. And finally, Resident Office moved to its own building of Resident Office Sri Aman in year 1994 until now. Sri Aman Division, which was formerly known as “Simanggang” or the second division in Sarawak was established on 1st June 1873. The name of “Sri Aman” was taken from the historical event of Sri Aman Declaration which was an agreement of peace and it was signed on 21st October 1973 between the government and communist.